High-flow nasal cannula therapy: A multicentred survey of the practices among physicians and respiratory therapists in Singapore. Issue 5 (September 2022) - Puah, Ser Hon; Li, Andrew; Cove, Matthew Edward; Phua, Jason; Ng, Vicky; Kansal, Amit; Tan, Qiao Li; Sahagun, Juliet Tolentino; Taculod, Juvel; Tan, Addy Yong-Hu; Mukhopadhyay, Amartya; Tay, Chee Kiang; et al.
Abstract: Background: Use of high-flow nasal cannula (HFNC) has become a regular intervention in the intensive care units especially in patients coming in with hypoxaemic respiratory failure. Clinical practices may differ from published literature. Objectives: The objective of this study was to determine the clinical practices of physicians and respiratory therapists (RTs) on the use of HFNC. Methods: A retrospective observational study looking at medical records on HFNC usage from January 2015 to September 2017 was performed and was followed by a series of questions related to HFNC practices. The survey involved physicians and RTs in intensive care units from multiple centres in Singapore from January to April 2018. Indications and thresholds for HFNC usage with titration and weaning practices were compared with the retrospective observational study data. Results: One hundred twenty-three recipients (69.9%) responded to the survey and reported postextubation (87.8%), pneumonia in nonimmunocompromised (65.9%), and pneumonia in immunocompromised (61.8%) patients as the top three indications for HFNC. Of all, 39.8% of respondents wanted to use HFNC for palliative intent. Similar practices were observed in the retrospective study with the large cohort of 63% patients (483 of the total 768 patients) where HFNC was used for acute hypoxaemic respiratory failure and 274 (35.7%) patients to facilitate extubation. The survey suggested that respondents would initiate HFNC at a lower fraction of inspired oxygen (FiO2 ), higher partial pressure of oxygen to FiO2 ratio, and higher oxygen saturation to FiO2 ratio for nonpneumonia patients than patients with pneumonia. RTs were less likely to start HFNC for patients suffering from pneumonia and interstitial lung disease than physicians. RTs also preferred adjustment of FiO2 to improve oxygen saturations and noninvasive ventilation for rescue. Conclusions: Among the different intensive care units surveyed, the indications and thresholds for the initiation of HFNC differed in the clinical practices of physicians and RTs.